2008
DOI: 10.1063/1.2979683
|View full text |Cite
|
Sign up to set email alerts
|

Order of magnitude enhancement in neutron emission with deuterium-krypton admixture operation in miniature plasma focus device

Abstract: The effect of varied concentrations of deuterium-krypton (D2–Kr) admixture on the neutron emission of a fast miniature plasma focus device was investigated. It was found that a judicious concentration of Kr in D2 can significantly enhance the neutron yield. The maximum average neutron yield of (1±0.27)×104 n/shot for pure D2 filling at 3 mbars was enhanced to (3.14±0.4)×105 n/shot with D2+2% Kr admixture operation, which represents a >30-fold increase. More than an order of magnitude enhancement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The increase in neutron yield by doping of deuterium with high z gases is observed in Filippov devices PF-3 (see Section 3.1.6), Sahand [437], a 1 MJ Mather device Gemini [436], and in smaller Mather type devices in Singapore [221,432] and University of Malaya [413,434]. It is not observed in DPF78 [431].…”
Section: Why Does the Neutron Yield Scaling Fail At High Bank Energies?mentioning
confidence: 97%
See 1 more Smart Citation
“…The increase in neutron yield by doping of deuterium with high z gases is observed in Filippov devices PF-3 (see Section 3.1.6), Sahand [437], a 1 MJ Mather device Gemini [436], and in smaller Mather type devices in Singapore [221,432] and University of Malaya [413,434]. It is not observed in DPF78 [431].…”
Section: Why Does the Neutron Yield Scaling Fail At High Bank Energies?mentioning
confidence: 97%
“…This fast miniature plasma focus (200 J, 2.4 µF, 27 nH, T 1/4~4 00 ns) was operated [432] with varied concentrations of D 2 -Kr admixtures. The maximum neutron yield with admixture operation increased by 30, 20, and 1.2 times for D 2 + 2% Kr (volumetric concentration), D 2 + 5% Kr, and D2 + 10% Kr, respectively, as compared to pure deuterium operation at 3 mbars.…”
Section: "Fmpf-1" In Singaporementioning
confidence: 99%
“…[9][10][11][12][13] The DPF device derives from a coaxial plasma gun that is filled with a low-pressure deuterium and tritium gas mixture to generate significant fusion reactions as the plasma compresses. Development of the DPF has traditionally focused on maximizing the total fusion neutron yield, [14][15][16] with more recent designs intended to increase portability and pulse repetition rates. [17][18][19][20] In this report, we describe the first efforts to constrain the neutron pulse duration while retaining as much of the total yield as possible.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has often cited plasma focus as an alternative magnetic fusion device due to the intense bursts of neutrons it produces when operated in deuterium (Cloth and Conrads 1977;Brunelli and Leotta 1982). However, the plasma focus device is not only a source of fusion neutrons (Mather 1965;Soto et al 2008;Verma et al 2009) but it also produces highly energetic ions (Sadowski et al 1988;Ghareshabani and Mohammadi 2012), relativistic electrons (Patran et al 2006), and abundant amount of soft and hard X-rays (Zakaullah et al 2002a, b;Shafiq et al 2003;Bhuyan et al 2004;Mohammadi et al 2007). One of the applications of plasma focus is a pump source for lasers (Kozlov et al 1974).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of impurities is of great interest for plasma focus community as it has been reported that their presence affects the X-ray (Verma et al 2008) and neutron yield (Verma et al 2009;Mohammadi et al 2011) from the plasma focus devices and also leads to the formation of the micropinch (Koshelev et al 1988), stabilized pinch column (Kies et al 2000), and promotion of slipping of the current sheath due to the Hall effect near the anode (Vikherev and Braginski 1986). According to Verma et al (2008Verma et al ( , 2009, the addition of high-Z krypton impurity to deuterium-enhanced X-rays and neutron yields many folds as it broadened the optimum pressure regime and stabilized the pinch for longer duration due to the slowing down of current sheath with a high-Z admixture operation, which was also observed in the PO-SEIDON plasma focus facility for a D 2 -Ar admixture operation (Schmidt et al 1994). The slowing down of current sheath speed in the radial phase was qualitatively deduced through an increase in the full width at halfmaximum of the dip in the current derivative signal.…”
Section: Introductionmentioning
confidence: 99%